2002
DOI: 10.1021/bi026243g
|View full text |Cite
|
Sign up to set email alerts
|

The βG156C Substitution in the F1-ATPase from the Thermophilic Bacillus PS3 Affects Catalytic Site Cooperativity by Destabilizing the Closed Conformation of the Catalytic Site

Abstract: Fluorescence titrations of the alpha(3)(betaG(156)C/Y(345)W)(3)gamma, alpha(3)(betaE(199)V/Y(345)W)(3)gamma, and alpha(3)(betaY(345)W)(3)gamma subcomplexes of TF(1) with nucleotides show that the betaG(156)C substitution substantially lowers the affinity of catalytic sites for ATP and ADP with or without Mg(2+), whereas the betaE(199)V substitution increases the affinity of catalytic sites for nucleotides. Whereas the alpha(3)(betaG(156)C)(3)gamma and alpha(3)(betaE(199)V)(3)gamma subcomplexes hydrolyze 2 mM A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…Bandyopadhyay et al (26) have suggested that endogenous nucleotides bound at the noncatalytic sites of ␤Y331W-EcF 1 are responsible for the apparent lack of asymmetry in the nucleotide binding in the absence of Mg 2ϩ reported earlier (24). Our results make it more likely that the main reason that the catalytic-site asymmetry had not been detected in the absence of Mg 2ϩ was the presence of Ϸ17 mM sulfate that competed with nucleotide binding to the high-affinity site.…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations
“…Bandyopadhyay et al (26) have suggested that endogenous nucleotides bound at the noncatalytic sites of ␤Y331W-EcF 1 are responsible for the apparent lack of asymmetry in the nucleotide binding in the absence of Mg 2ϩ reported earlier (24). Our results make it more likely that the main reason that the catalytic-site asymmetry had not been detected in the absence of Mg 2ϩ was the presence of Ϸ17 mM sulfate that competed with nucleotide binding to the high-affinity site.…”
Section: Discussionmentioning
confidence: 43%
“…2, circles) show that the catalytic sites of ␤Y331W-dEcF 1 do exhibit asymmetry in nucleotide binding in the absence of Mg 2ϩ . Different affinities of the catalytic sites for a nucleotide in the absence of Mg 2ϩ have also been observed with the homologous ␤Y341W-mutant ␣ 3 ␤ 3 ␥-subcomplex of TF 1 (26). We did not attempt to measure K d values for MgATP as has been done previously (18,27) because the rapid formation of catalytic site ADP makes it uncertain what nucleotide affinity is being measured.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Consequently, the total binding energy was compared with the binding free energy of the complexes using the fluorescence spectroscopy quenching method[20], [21]. As shown in Table 2 , the Molecular Mechanics Generalized Born Surface Area (MM-GBSA) calculation predicted that mutants wound bind more weakly to the inhibitors than to the wild type (WT)-HL systems with estimated ΔG bind values of −8.4, −4.2, −1.4, −8.9, −4.0, −2.3 kcal/mol for R104A-OLG, R104A-ORA, R104A-ORB, G126A-OLG, G126A-ORA, and G126A-ORB, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…A 280-nm excitation wavelength with a 5-nm band-pass and a 345-nm emission wavelength with a 10-nm band-pass were used for the measurements. The details of the protocol used to perform the measurements were as previously described (Bandyopadhyay et al, 2002; Jurasekova et al, 2009). …”
Section: Methodsmentioning
confidence: 99%